2020
DOI: 10.3390/cancers12061388
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ATM Increases the Radiosensitivity of Uveal Melanoma Cells to Photons and Protons

Abstract: Treatment of uveal melanoma (UM) is generally successful, with local primary tumour control being at 90%–95%. Localized radiotherapy in the form of plaque brachytherapy or proton beam radiotherapy is the most common treatment modality in the UK. However, the basic mechanisms of radiation response, DNA repair and tissue reactions in UM have not been well documented previously. We have investigated the comparative radiosensitivity of four UM cell lines in response to exogenous radiation sources (both X-rays and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Mel270 originated from a recurrent tumor after prior irradiation and thus escaped radiation therapy [7]. Previous studies have confirmed that Mel270 spheroids are less responsive to radiation and electrochemotherapy with bleomycin compared to other UM cell lines 92-1, UPMD2, or UPMM3 [32,36]. However, in the present study, the tumor control of Mel270 spheroids was achieved by carvedilol treatment.…”
Section: Discussioncontrasting
confidence: 48%
“…Mel270 originated from a recurrent tumor after prior irradiation and thus escaped radiation therapy [7]. Previous studies have confirmed that Mel270 spheroids are less responsive to radiation and electrochemotherapy with bleomycin compared to other UM cell lines 92-1, UPMD2, or UPMM3 [32,36]. However, in the present study, the tumor control of Mel270 spheroids was achieved by carvedilol treatment.…”
Section: Discussioncontrasting
confidence: 48%
“…The latter cell type was seen particularly in those mUM that had undergone necrosis and were associated with a desmoplastic reaction ( Figure 6 ). Plasma and CD20+ B-cells have been described in primary UM, albeit as focal aggregates in small quantities, and in some cases associated with necrosis [ 26 , 48 , 49 , 50 ]. Our observations may thus explain the relatively poor responses to trialled adoptive transfer of autologous TIL-based therapies in patients with mUM [ 51 ] and emphasise the urgent need to refine T-cell therapy in this setting [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our data, Moschos et al and Hussain et al suggested an increase in radioresistance based on a thorough ATM-related DNA repair. Further analysis should be done to check the role of ATM in the radiation response of cancer and nonmalignant cell lines [20,62].…”
Section: Discussionmentioning
confidence: 99%